Skip-beat! 12 - Nakamura, Yoshiki (Shojo beat manga., 2008)
"Kyoko's determination to help Ren continues as she lends a friendly ear--in her chicken suit. Ren opens up and confides in Chicken Bo, but is Kyoko really ready to deal with his lovelorn confession? To make matters worse, Ren's been given an ultimatum by the LME president, and if he can't act right by the end of the week, he's out on his ear!"--p. [4] of cover.